Semiquantitative theory for high-field low-temperature properties of a distorted diamond spin chain - Derzhko, O.; Richter, J.; Krupnitska, O. (Condensed Matter Physics, 2012)
We consider the antiferromagnetic Heisenberg model on a distorted diamond chain and use the localized-magnon picture adapted to a distorted geometry to discuss some of its high-field low-temperature properties. More specifically, in our study we assume that the partition function for a slightly distorted geometry has the same form as for ideal geometry, though with slightly dispersive one-magnon energies. We also discuss the relevance of such a description to azurite.